Viscoelastic Finite Line Contact of Thin Bonded Layered Solids of Low Elastic Modulus - Vasilis Votsios; Patricia Johns-Rahnejat; Homer Rahnejat (Applied Sciences, 2020)
A new finite element-based contact mechanics analysis of layered viscoelastic solids of low elastic modulus is presented. The methodology is based on the Maxwell viscoelastic element, with stress relaxation taken into account by the Prony series’ representation of the bulk and shear material moduli. Simultaneous solutions for deviatoric and volumetric stresses were obtained under instantaneous elastic and subsequent viscoelastic relaxation, at multiples of the relaxation time of a Highly Filled Carbon Polymer (HFCP) layer. The results of the analysis were validated by a constructed, multi-layered sandwich sensor comprising the HFCP sensing elements covered by a protective silicone rubber surface of very low elastic modulus. The combined numerical-experimental approach, and the validated viscoelastic layered contact mechanics represent the original contribution of this paper, not hitherto reported in literature.